Modelagem matemática do padrão de crescimento e seleção de genótipos de Schizolobium parahyba var. amazonicum (Huber ex. Ducke) Barneby - Botin, Andréia Alves (2022)
Schizolobium parahyba var. amazonicum (Huber ex. Ducke) Barneby, popularly known as paricá, is a naturally occurring plant in the Amazon region. Wood has several applications in the market, as the plant has a straight trunk and a smooth surface. The species can be planted in recovery areas, mixed plantations, among others, due to its rapid growth. The species has great potential and importance for the Brazilian market, however, there is no availability of genetically improved material, selected for the conditions of Mato Grosso. In this sense, the present work aimed, in the first article, to analyze the growth in diameter and height of paricá in a plantation in the municipality of Sinop-MT, comparing nonlinear growth models adjusted to these growth parameters and, in the second article, to select the best families of paricá halfsiblings for the variables diameter to breast height (DAP) and total height (Ht) evaluated in 10 measurements and select the best individual trees based on the variables genotypic values of these variables aiming at cloning these trees. The experimental design was randomized blocks, consisting of 4 blocks and 58 families, in 4x4 m spacing, with 5 plants per plot. In the first chapter, the growth analysis was performed in diameter and height of planting during the first one and a half year of age of the settlement. For this analysis, the nonlinear regression models were adjusted and the average daily increment for the species was analyzed in the variables base stem diameter (DC), diameter breast height (DAP) and total height (H). Among the models tested, it is possible to indicate brody's models to predict growth in DC and the logistics function for DAP and H. The species presented average increments of 0.12 mm day-1 for DC, 0.13 mm day-1 in DAP and 1.15 cm day-1 for H. In the second chapter, the adaptability and stability were verified, by the REML/BLUP (Restricted Maximum Likelihood/Best Linear Unbiased Prediction) procedure, at the level of half-sibling families, for the data collected between September 2018 and August 2020, for a total of 10 measurements. The mixed model method (REML/BLUP) proved to be adequate for the estimation of genetic parameters and the prediction of genetic values for the species, within the conditions of the experiment. The families selected according to the harmonic mean method of relative performance of predicted genetic values (MHPRVG), based on DAP and H were: 3, 5, 16, 17, 18, 21, 22, 24, 28, 30, 32, 34, 35, 36, 56, 57 and 58. The best individual for the character DAP was tree 2 of block 1 of family 10 with an average of 8.44 cm and for the height character was tree 5 of block 1 of family 2 with an average of 8.40 m. The gains obtained with the selection can reach 22.55% for THE DAP and 31.39% for H. With this study it was possible to verify that there is genetic variability in paricá, and that the population can be used as an orchard for seed collection and/or clonal garden.